Transformative experience - Douglas, C (Auckland, NZ: AGM Publishing, 2009)
Trans-Form-ers was a joint venture for Architecture Week, between the University of Auckland School of Architecture and Planning, the Unitec School of Architecture and Landscape Architecture, the Unitec Bachelor of Interior Design, and AUT's Department of Spatial Design. Students from the three schools were challenged to design mobile déployable pavilions that could be taken in convoy from Unitec's suburban site to the old ARC vehicle maintenance sheds near Victoria Park.
Keywords: Architecture; Auckland; Pavilion; Exhibition